O Processo de gestão, orientação e supervisão escolar: uma análise do trabalho pedagógico no Centro de Recuperação Regional de Abaetetuba - CAMÕES, Josiane Sena (2019)
The objective of this study is to analyze the pedagogical action of School Management, Guidance and Supervision at the Regional Recovery Center of Abaetetuba, highlighting the contributions of the pedagogue within the penitentiary system. The analysis was guided by the legal aspects and the reconstruction of the historical context, showing the emergence and the need of education professionals in the penitentiary system. In the theoretical referential we analyze the field of action of the pedagogues and the public policies of prison education. An interview with open questions was applied to the pedagogical teacher of the CRRAb and an interview with the pedagogical coordinator. The research was guided by bibliographical analyzes, following the idea of some authors who defend the penitentiary education as necessary for a possible re-education of the prisoner and thus, to return it to society. Through this research, we can highlight the importance of pedagogical work in directing and coordinating the educational aspects in the CRRAb. The research evidenced the lack of materials and adequate physical structure to carry out the educational activities and lack in the offer of training and continuing education of teachers. It can be considered that prison education is still moving slowly and that public policies for the sector are deficient.